Influence of nitrate and nitrite concentration on N(2)O production via dissimilatory nitrate/nitrite reduction to ammonium in Bacillus paralicheniformis LMG 6934 - Sun, Yihua (Microbiologyopen, 2018)
Until now, the exact mechanisms for N(2)O production in dissimilatory nitrate/nitrite reduction to ammonium (DNRA) remain underexplored. Previously, we investigated this mechanism in Bacillus licheniformis and Bacillus paralicheniformis, ubiquitous gram‐positive bacteria with many industrial applications, and observed significant strain dependency and media dependency in N(2)O production which was thought to correlate with high residual NO (2) (−). Here, we further studied the influence of several physicochemical factors on NO (3) (−) (or NO (2) (−)) partitioning and N(2)O production in DNRA to shed light on the possible mechanisms of N(2)O production. The effects of NO (3) (−) concentrations under variable or fixed C/N‐NO (3) (−) ratios, NO (2) (−) concentrations under variable or fixed C/N‐NO (2) (−) ratios, and NH (4) (+) concentrations under fixed C/N‐NO (3) (−) ratios were tested during anaerobic incubation of soil bacterium B. paralicheniformis LMG 6934 (previously known as B. licheniformis), a strain with a high nitrite reduction capacity. Monitoring of growth, NO (3) (−), NO (2) (−), NH (4) (+) concentration, and N(2)O production in physiological tests revealed that NO (3) (−) as well as NO (2) (−) concentration showed a linear correlation with N(2)O production. Increased NO (3) (−) concentration under fixed C/N‐NO (3) (−) ratios, NO (2) (−) concentration, and NH (4) (+) concentration had a significant positive effect on NO (3) (−) (or NO (2) (−)) partitioning ([N–NH (4) (+)]/[N–N(2)O]) toward N(2)O, which may be a consequence of the (transient) accumulation and subsequent detoxification of NO (2) (−). These findings extend the information on several physiological parameters affecting DNRA and provide a basis for further study on N(2)O production during this process.